(untitled) (Bodhi Path, 2022)
Originated by Lord Buddha, Buddhism is a religion of the Shramana tradition. In the Vedic tradition, where the four- dharma, artha (money), kama (action) and moh (attachment) play an important role, additionally there is an established age-based-system.There exist fix age ranges for education and celibacy, house hold, getting ready for renunciation, and finally renunciation. Such a system is not found in the Buddhist tradition, it is called nivrita pradhan. Considering enlightenment as the ultimate goal, a code of conduct was created. In the 6th century BC, Buddha opposed violent sacrifices and established the importance of non-violence in society, which proved to be a boon for humans suffering from physical ailments.